2014
DOI: 10.1007/s12038-013-9403-y
|View full text |Cite
|
Sign up to set email alerts
|

Competing views on cancer

Abstract: Despite intense research efforts that have provided enormous insight, cancer continues to be a poorly understood disease. There has been much debate over whether the cancerous state can be said to originate in a single cell or whether it is a reflection of aberrant behaviour on the part of a ‘society of cells’. This article presents, in the form of a debate conducted among the authors, three views of how the problem might be addressed. We do not claim that the views exhaust all possibilities. These views are (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 157 publications
(182 reference statements)
2
41
0
1
Order By: Relevance
“…These genes were significantly enriched in developmental processes ( Figure 1D), implicating the importance of epigenetic repression of certain developmental programs in tumorigenesis. While somatic mutations have been widely considered as main drivers of tumors, amounting evidence has suggested that tumorigenesis is largely affected by surrounding environments and driven by aberrant epigenetic regulation during development [10,11] Our results provided supporting evidence that epigenetic aberration in development may be associated with adenocarcinoma.…”
Section: Discussionsupporting
confidence: 73%
“…These genes were significantly enriched in developmental processes ( Figure 1D), implicating the importance of epigenetic repression of certain developmental programs in tumorigenesis. While somatic mutations have been widely considered as main drivers of tumors, amounting evidence has suggested that tumorigenesis is largely affected by surrounding environments and driven by aberrant epigenetic regulation during development [10,11] Our results provided supporting evidence that epigenetic aberration in development may be associated with adenocarcinoma.…”
Section: Discussionsupporting
confidence: 73%
“…A competing perspective is that of cancer as a circuit disease-a disorder of the complex biophysical, transcriptional, and epigenetic dynamics that regulate cellular state and the ability of cells to cooperate in vivo [6][7][8]. Under this view (sometimes called the tissue organization field theory or TOFT, [9,10]), cancer is akin to a traffic jam [11]-the problem is not a permanent discrete alteration within a founder cell and all of its clonal descendants, but an undesirable stable attractor in the complex network of controls that normally guides anatomical homeostasis [12].The relative merits of the two models have been discussed extensively [10,[13][14][15][16][17] …”
mentioning
confidence: 99%
“…Currently, SMT and TOFT are recognized to be different paradigms by independent researchers (Wolkenhauer and Green 2013;D'Anselmi et al 2011;Sonnenschein et al 2014b;Satgé and Bénard 2008;Prehn 2005;Schwartz et al2002;Baker et al 2010;Laforge et al 2005;Longo and Montévil 2014;Levin 2012;Smythies 2015;Tarin 2011).…”
Section: Epistemological Bases Of Current Cancer Theoriesmentioning
confidence: 99%